Are serum levels of inflammatory markers associated with the severity of symptoms of bipolar disorder? - Wu, Xiuhua; Chen, Zhongcheng; Liao, Yingtao; Yang, Zhihua; Liang, Xiaolin; Guan, Nianhong; Gan, Zhaoyu (Frontiers in Psychiatry, 2023)
Background: To explore the relationship between serum levels of inflammatory markers and symptomatic severity of bipolar disorder (BD). Material and Methods: A cross-sectional study was conducted on 126 BD patients with current depressive episode (BDD), 102 BD patients with current mixed or (hypo)manic episode (BDM) and 94 healthy controls (HC). All participants were drug-naïve and had no current active physical illness associated with inflammatory response or history of substance abuse. Fasting serum levels of CRP, leptin (LEP), adiponectin (ADP), visfatin (VIS), TNF-α, IL-2, IL-6, IL-10, IL-17), and monocyte chemoattractant protein-1 (MCP-1) were measured with enzyme-linked immunosorbent assay (ELISA). Symptomatic severity of BD was assessed with HAMD-17 and YMRS. Generalized linear model was used to determine the association between the serum levels of inflammatory markers and symptomatic severity of BD. Results: The serum levels of IL-6, IL-10 and IL-17, and the IL-6/IL-10 ratio were significantly lower in mild BDD than in HC. In moderate BDD, the serum levels of MCP, IL-6 and IL-17 were significantly lower than in HC. In severe BDD, the serum level of ADP, MCP-1, IL-10 and IL-17and the IL-17/IL-10 ratio were significantly lower than in HC. The serum levels of TNF-α and the IL-6/IL-10 ratio were significantly higher in mild BDM than in HC. In moderate BDM, the serum level of VIS, IL-2, and IL-17 were significantly higher than in HC, but the IL-6/IL-10 ratio was significantly lower than in control. In severe BDM, the serum levels of IL-6 and IL-17 and the ratios of IL-6/IL-10 and IL-17/IL-10 were significantly lower than in HC, but the neutrophil/lymphocyte ratio was significantly higher than in HC. Conclusions: In BDD, immune-inhibition is persistently predominant, while in mild-to-moderate BDM, immune system is activated but inhibited in servere BDM. The dynamic change of serum inflammatory markers suggests that alteration of peripheral inflammatory markers in BD is state-dependent instead of trait-marked.